Pengembangan Metode Penilaian Mandiri Kualitas Data Rutin Di Dinas Kesehatan Kota Surakarta - Puguh Ika Listyorini; Mursid Raharjo; Farid Agushybana (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2017)
Data are the basis to make a decision and policy. The quality of data is going to produce a better policy. The quality assessment methods nowadays do not include all indicators of data quality. If the indicators or assessment criteria in the quality assessment methods are more complete, the level of assessment methods of the data will be higher. The purpose of this study is to develop the method of independent assessment of routine data quality in Surakarta Health Department which is previously performed using the data quality assessment of PMKDR and HMN methods firstly.The design of this study is research and development (R&D) that has been modified into seven steps, namely formulating potential problems, collecting the data, designing the product, validating the design, fixing the design, testing the product, and fixing the product. The subjects consisted of 19 respondents who are managers of data in Surakarta Health Department. Data analysis method used is content analysis.The assessment results show that, in the pilot phase of the development of data quality assessment methods which have been developed, it is basically successful, or it can be used. The results of the assessment of the quality of the data by the developed method is the quality of data collection which is very adequate, the quality of data accuracy which is poor, the quality of data that consistency exists but is inadequate, the quality of the actuality of the data which is very adequate, the quality of periodicity data that is inadequate, the quality of the representation of the data that is very adequate, and sorting the data which is very adequate.It needs a commitment from Surakarta Health Department to take advantage of the development of these methods to assess the quality of data to support the availability of information, decision-making and planning of health programs. It also calls for the development of this research by conducting all stages of the steps of R&D so that the final result of the method development will be better.